Adenoiditis: A Modern Look In Diagnostics And Treatment - J.Kh. Razzokov; J.A. Djuraev (International Scientific and Current Research Conferences, 2021)
Most of the visits of parents with children to an otorhinolaryngologist are associated with frequently recurring, protracted and chronic diseases of the ENT organs. The most common complaints are a runny nose, difficulty breathing through the nose, and a cough that does not go away for a long time and is often repeated. Some patients have complications of the common cold: sinusitis, recurrent acute catarrhal, less often purulent otitis media, tubo otitis, secretory otitis media with signs of hearing loss, exacerbation of chronic purulent otitis media, tracheitis, bronchitis, stenosing laryngotracheitis. Failure to treat ENT pathologies, short intervals between diseases, frequent acute respiratory infections are also a reason for consulting an ENT doctor. When interviewing parents, it was found that rhinopharyngitis, allergic rhinitis, and adenoiditis are most often diagnosed. For a clearer understanding of the nature and methods of treatment of these diseases, it is necessary to characterize those pathological changes that are observed in the upper respiratory tract, i.e., in the nasal cavity, nasopharynx and pharynx.